(untitled) (Journal of Current and Advance Medical Research, 2023)
Background: The integration of clinical, radiographic and pathology findings-based information has long been intrinsic to diagnosis and proper management. Objective: The purpose of study was to observe the imaging features of hybrid and non-hybrid Fibro-Osseous Lesion at Maxillofacial Area among the participants. Methodology: This cross-sectional study was conducted in the Department of Oral & Maxillofacial Surgery at Dhaka Dental College & Hospital, Dhaka, Shaheed Suhrawardy Hospital, Dhaka and Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh from January 2004 to December 2005. Participants were selected for the study who attended into outpatient and inpatient departments with fibro-osseous lesions during study period, irrespective of age & sex. A standardized structured data collection sheet was used to collect necessary information of the study history of the patients and clinical examination; radiology, histopathology and macroscopic findings of surgical specimen were recorded. Result: Most of the patients’ age was between 11 to 30 for both hybrid and non-hybrid form. Among them average age of the patients was 24.98 years (±SD 13.4).The mean age of the Non-hybrid group is 26.35 (±SD 13.92) years and mean age of Hybrid group is 17.17 (± SD 6.18) years. In hybrid form most of the radiological pattern was mixed type (83.3%) but in non-hybrid form all other mentioned radiological character were found. In cross-section of surgical specimens of hybrid form cavitation were found in all cases (100.0%) but it was not detected in a single case in non-hybrid form (0.0%). Multicystic haemorrhagic spaces were seen in 100.0% cases of hybrid form whereas none was detected in non-hybrid. Conclusion: The Imaging and histomorphology of fibro-osseous lesion is very important tools to proper diagnosis and management. Journal of Current and Advance Medical Research, July 2022;9(2):79-82